Strategic importance of functional level strategies as effective tools for the achievement of organizational goals - Agwu, M. E.; Onwuegbuzie, Henrietta (Archives of Business Research, 2017)
Present business environment is characterized by high levels of competition, dynamism and technological sophistication. This is especially challenging to organizational managers since they have to design and implement strategies that can achieve and sustain competitive advantages. Consequently, the topic functional level strategy plays a pivotal role as organizations aim at gaining industry leadership. This study set out to investigate functional level strategy as a tool for achieving organizational goals. Gaining insight from existing literature and theoretical models four hypothesis were developed and investigated through the survey of the strategic business units of selected financial organizations. Copies of well-structured questionnaire were administered. Findings revealed that there is a relationship between marketing strategy and customer satisfactions, the price of a product and consumer purchasing such product. It also indicated that effective productivity facilitation of the firm resources help expand the firm. The authors recommends that in order to be more competitive, organizational managers must be strategically aware of how effective control of the various functional departments in the organization help organization to be aware of customer needs and offer unique products and services that satisfy such needs.